2019
DOI: 10.26794/2304-022x-2019-9-1-76-95
|View full text |Cite
|
Sign up to set email alerts
|

Human-Oriented Approach in Forming of Key Competences of Civil Servants in the Conditions of Digital Transformation of the Economy

Abstract: Статья посвящена вопросам применения человеко-ориентированного подхода при определении компетенций государственных гражданских служащих и направлений развития их квалификации. Цель исследования-разработка модели ключевых компетенций государственных гражданских служащих с учетом требований должностных регламентов, квалификационных требований к профессиональным знаниям и навыкам государственных гражданских служащих, отраженных в нормативных и правовых документах, а также тенденций компетентностно-ориентированног… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Lazukova among Perm state civil servants [11] showed a high (more than 70 %) level of satisfaction of respondents-officials with their position, only a third of them were candidates for official growth, of which more than half associate career dissatisfaction with the lack of prospects for promotion. Research conducted in 2018 [4] also showed that the majority of respondents (75%) are satisfied with their career in public service, a third have high career ambitions, more than half do not see a real prospect of career growth, only a third of respondents are confident in official growth.…”
Section: Values Indicatormentioning
confidence: 99%
“…Lazukova among Perm state civil servants [11] showed a high (more than 70 %) level of satisfaction of respondents-officials with their position, only a third of them were candidates for official growth, of which more than half associate career dissatisfaction with the lack of prospects for promotion. Research conducted in 2018 [4] also showed that the majority of respondents (75%) are satisfied with their career in public service, a third have high career ambitions, more than half do not see a real prospect of career growth, only a third of respondents are confident in official growth.…”
Section: Values Indicatormentioning
confidence: 99%
“…Актуальность исследования педагогических основ подготовки кадров для государственной службы обусловлена тем, что их профессиональное развитие и становление в современных социально-экономических условиях является важнейшей частью не только профессиональной карьеры чиновника, но и развития общества. При [3]. Социальный институт наставничества, как считают И.А.…”
Section: Introductionunclassified
“…Бондалетов рассматривают электронное или цифровое обучение как важный механизм объективного контроля полноты освоения служащими актуальных знаний и навыков, а также как создание оптимальных условий получения знаний, умения и навыков в удобное время и в субъективном образовательном пространстве [2]. Е.В.Васильева и др., в формировании ключевых компетенций государственных гражданских служащих в условиях цифровой трансформации экономики выделяют человеко-ориентированный подход или субъектно-ориентированный [3].…”
Section: Introductionunclassified